Mississippian Mortuary Practices : Beyond Hierarchy and the Representationist Perspective - Mainfort, R. C. (Robert C.); Sullivan, Lynne P. (Book collections on Project MUSE., 2010)
The residents of Mississippian towns principally located in the southeastern and midwestern United States from 900 to1500 A.D. made many beautiful objects, which included elaborate and well-crafted copper and shell ornaments, pottery vessels, and stonework. Some of these objects were socially valued goods and often were placed in ritual context, such as graves. The funerary context of these artifacts has sparked considerable study and debate among archaeologists, raising questions about the place in society of the individuals interred with such items, as well as the nature of the societies i.